A novel process concept for the three step Boscalid® synthesis. Issue 63 (16th June 2016) - Volovych, I.; Neumann, M.; Schmidt, M.; Buchner, G.; Yang, Ji-Yoon; Wölk, J.; Sottmann, T.; Strey, R.; Schomäcker, R.; Schwarze, M.
Abstract : A three phase microemulsion system was applied for a more sustainable synthesis of the fungicide Boscalid®. Abstract : Nowadays, the development of chemical processes using environmentally friendly solvents is of high importance. As an alternative to conventional reaction media based on organic solvents, we show a novel aqueous surfactant-based process concept which is used for the three step synthesis of the fungicide Boscalid®. By applying three phase microemulsion systems for the Suzuki coupling reaction, the first step within the Boscalid® synthesis, a simple product and catalyst separation can be achieved, whereby the water-soluble homogeneous Pd/SPhos catalyst complex can be reused several times. Together with an easily recyclable heterogeneous PtIr@TiO2 catalyst, which is applied for the hydrogenation reaction in the second step, followed by base-assisted condensation to the final product Boscalid® in the third step, overall yields up to 90% are achievable for the whole reaction sequence. This result was obtained without any purification step in between that requires the use of further solvents. In this way the total synthesis costs can be reduced and solvent wastage can be avoided.